2004
DOI: 10.1038/sj.embor.7400093
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the conserved domain of ANAC, a member of the NAC family of transcription factors

Abstract: The structure of the DNA-binding NAC domain of Arabidopsis ANAC (abscisic-acid-responsive NAC) has been determined by Xray crystallography to 1.9 Å resolution (Protein Data Bank codes 1UT4 and 1UT7). This is the first structure determined for a member of the NAC family of plant-specific transcriptional regulators. NAC proteins are characterized by their conserved N-terminal NAC domains that can bind both DNA and other proteins. NAC proteins are involved in developmental processes, including formation of the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
323
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 393 publications
(339 citation statements)
references
References 32 publications
11
323
0
5
Order By: Relevance
“…Subsequently, the results of ethylene glycol disuccinate di(Nsuccinimidyl) ester (EGS) cross-linking confirmed this observation and demonstrated that such a dimeric architecture does not dissociate, even at very high salt concentrations (5 M NaCl). These results indicate that the dimeric form should form the functional unit of the SNAC1 NAC domain, which is consistent with the previously reported results on the ANAC NAC domain (Ernst et al, 2004) and our knowledge that the dimerization of DNA binding domains is common and can function in modulating the DNA binding specificity (Müller, 2001). In the crystal structure, two molecules of the SNAC1 NAC domain, which are related by a crystallographic twofold axis, form a butterfly shaped homodimer (Fig.…”
Section: Dimeric Assembly Of Snac1 Nac Domainsupporting
confidence: 93%
See 4 more Smart Citations
“…Subsequently, the results of ethylene glycol disuccinate di(Nsuccinimidyl) ester (EGS) cross-linking confirmed this observation and demonstrated that such a dimeric architecture does not dissociate, even at very high salt concentrations (5 M NaCl). These results indicate that the dimeric form should form the functional unit of the SNAC1 NAC domain, which is consistent with the previously reported results on the ANAC NAC domain (Ernst et al, 2004) and our knowledge that the dimerization of DNA binding domains is common and can function in modulating the DNA binding specificity (Müller, 2001). In the crystal structure, two molecules of the SNAC1 NAC domain, which are related by a crystallographic twofold axis, form a butterfly shaped homodimer (Fig.…”
Section: Dimeric Assembly Of Snac1 Nac Domainsupporting
confidence: 93%
“…The crystal structure of the conserved NAC domain of stressresponsive NAC1 (SNAC1) (residues Met1-Lys174) was determined by the molecular replacement (MR) method using the crystal structure of the NAC domain of ANAC (PDB code: 1UT4) (Ernst et al, 2004) as the initial searching model. The final structure was refined to 2.5 Å resolution with a final R work value of 23.1% (R free = 26.7%).…”
Section: Monomer Folding Of Snac1 Nac Domainmentioning
confidence: 99%
See 3 more Smart Citations